Pemahaman Proposional Tentang Mahram Sebagai Pendamping Dalam Perjalanan Perempuan - Sri Handayana; Arif Budiman (Institut Agama Islam Negeri Metro, 2020)
This article is intend on providing contextual understanding on Muslim women travelling attitude by investigating some hadith texts as well as describing historical reading and substantive meaning raised by those hadith. Muslim scholars’ perspective on mahram (consanguinity) role may vary despite the fact that they refer to the similar prophetic traditions. Classical ulama who tend to understand the hadith textually stated that it was banned on women for travel alone without companion. It is not surprising because their understanding strongly reflected social-cultural situation in that era. However, language approach reveal the idea behind the text that diverse structure of prohibition for women to travel without mahram drive different purposes. This drives to conviction that women were not allowed to travel without their relatives due to safety and propriety. Thus, things have to put into consideration are that it does not matter for women travelling by themselves providing that the security is assured and women do not culturally break moral behavior.